MACHINE AND ORGANIC PARADIGMS: APPROACHES TO ANALYZING ORGANIZATIONS - Bambang Riyanto L. S; Gugup Kismono (Faculty of Economics and Business, Universitas Gadjah Mada, 1998)
This paper compares and contrasts the two popular ways of seeing an organization, machine and organic paradigms. It is argued that a better understanding of these different characteristics is a necessary requirement to obtain a more accurate assessment about organizational problems and or potentials. The both paradigms concern with ways to protect organizations from any tendency of dysfunction; they represent rational attempts to exploit the resources of the organizations in the most efficient manner, given their environmental constraints. Furthermore, both offer methods to divide organizational activities in an ordered (or hierarchical) manner. However, the two paradigms differs in, at least, five important respects, namely the criteria of effectiveness (machine: maximize efficiency and production vs. organic: maximize flexibility, satisfaction and development); organizational structure (machine: functional/division of labor vs. organic: deemphasis of specialization); assumptions about human resource (machine: extrinsically motivated vs. organic: intrinsically motivated); control mechanism (machine: rigid standards vs. organic: create selfdevotion). Using the contingency approach, the paper suggests that the machine paradigm ought to be adopted in analyzing organizations living in a more stable environment, whereas the organic paradigm should be adopted in analyzing organizations living in a more turbulent environment.